Strategic Planning of Early Childhood Education Principals in Enhancing Educational Quality and Institutional Competitiveness - Syaiful Arif Manurung; Topan Iskandar; Chanda Chansa Thelma (Al-Qalam Institute, 2026)
Early childhood education institutions are increasingly required to strengthen educational quality while maintaining institutional competitiveness in dynamic educational environments. This study aims to analyze the strategic planning practices of the principal of TK Asasi Tanjungbalai in improving educational quality and institutional competitiveness. The research employed a qualitative descriptive case study design, involving in-depth interviews, participatory observation, and documentation analysis. Data were analyzed using the interactive model of data reduction, data display, and conclusion verification to ensure credibility through triangulation. The findings reveal three major themes. First, the principal implemented a vision-driven strategic alignment model that integrated long-term goals with curriculum development, teacher professional growth, and resource allocation. Second, participatory strategic governance was established through collaborative planning forums involving teachers, staff, and parents, strengthening collective ownership and accountability. Third, institutional branding strategies were systematically developed through program innovation, community partnerships, and digital promotion, enhancing public trust and enrollment growth. These findings contribute to the literature on strategic leadership in early childhood education by providing an integrated model linking planning, participation, and branding. It is recommended that early childhood institutions institutionalize participatory strategic planning frameworks to ensure sustainable quality improvement.